PERBANDINGAN JENIS ELEKTRODA E7016 DAN E7018 TERHADAP SIFAT MEKANIK HASIL PENGELASAN SMAW - Fachrul Juniarianto; Dwisetiono (Hexagon Jurnal Teknik dan Sains, 2021)
This comparison aims to determine the mechanical properties and microstructure as well as the relationship between the two results of SMAW welding with variations in welding current using E7016 and E7018 electrodes. The use of different electrodes and currents in the welding process affects the physical and mechanical properties of the weld. This study aims to determine the results of the welds, microstructure, hardness distribution and tensile strength of the type of electrode and welding current. The research object of welding used is low carbon steel.